Effect of intra-articular injection of intermediate-weight hyaluronic acid on hip and knee cartilage: in-vivo evaluation using T2 mapping. - Ferrero, Giulio; Sconfienza, Luca Maria; Fiz, Francesco; Fabbro, Emanuele; Corazza, Angelo; Dettore, Daniele; Orlandi, Davide; Castellazzo, Carlo; Tornago, Stefano; Serafini, Giovanni (European Radiology, 2018)
Objectives: We used T2 mapping to quantify the effect of intra-articular hyaluronic acid administration (IAHAA) on cartilage with correlation to clinical symptoms.Methods: One hundred two patients with clinical and MRI diagnosis of hip or knee grade I-III chondropathy were prospectively included. All patients received a standard MRI examination of the affected hip/knee (one joint/patient) and T2-mapping multiecho sequence for cartilage evaluation. T2 values of all slices were averaged and used for analysis. One month after MR evaluation 72 patients (38 males; mean age 51±10 years) underwent IAHAA. As a control group, 30 subjects (15 males; 51 ± 9 years) were not treated. MR and WOMAC evaluation was performed at baseline and after 3, 9, and 15 months in all patients.Results: T2 mapping in hyaluronic acid (HA) patients showed a significant increase in T2 relaxation times from baseline to the first time point after therapy in knees (40.7 ± 9.8 ms vs. 45.8 ± 8.6 ms) and hips (40.9 ± 9.7 ms; 45.9 ± 9.5 ms) (p < 0.001). At the 9- and 15-month evaluations, T2 relaxation dropped to values similar to the baseline ones (p < 0.001 vs. 3 month). The correlation between T2 increase and pain reduction after IAHAA was statistically significant (r = 0.54, p < 0.01) in patients with grade III chondropathy.Conclusions: T2 mapping can be used to evaluate the effect over time of IAHAA in patients with hip and knee chondropathy.Key Points: • T2 relaxation times change over time after hyaluronic acid intra-articular administration • T2 relaxation times of the medial femoral condyle correlate with WOMAC variation • T2 relaxation times are different between Outerbridge I and II-III.